The validity and reliability of a hydraulic resistance device for assessing resisted sprint time - Sašek, M.; Cvjeticanin, O.; Šarabon, N. (Frontiers in Sports and Active Living, 2024)
Introduction: The aim of this study was to assess the validity and reliability of a hydraulic resistance device (HRD) for monitoring sprint split times under different loads within and between sessions.